This is because logarithm has its own set of properties that is different from algebra. The term log(3x - 1) is equivalent to log 3x/log 1. If we continue to rearrange and find x, the solution would be:
log(3x - 1) = log28
log 3x/log 1 = log 28
log 3x = log 28 * log 1 = 0
3x = 10⁰ = 1
3x = 1
x = 1/3
<em>So, that means 3x - 1 = 3(1/3) - 1 = 0.</em>
Answer:
28/81
Step-by-step explanation:
4/9 x 7/9; 2 negatives = a positive so the answer is 28/81
Hope this helps! :)
Answer:
I think the answer is c
Step-by-step explanation:
hope it helps